2012
DOI: 10.1590/s0104-11692012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Work organization and the health of bank employees

Abstract: The Brazilian banking sector has undergone an intense restructuring process and taken a leading position in the incorporation of new technologies and organizational innovations.Computerization in the industry, in association with forms of work organization, has resulted in changes that reflect on the workers' health. Based on the theoretical and methodological frameworks of historical and dialectical materialism, this qualitative study investigates the work conditions of bank employees in order to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…Computerization in the industry, in association with forms of work organization, has resulted in changes that reflect on the workers’ health. [ 11 ] Long hours of work, dealing with different situations, interpersonal relationship within workplace and people along with or without their family and personal problems will lead to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Computerization in the industry, in association with forms of work organization, has resulted in changes that reflect on the workers’ health. [ 11 ] Long hours of work, dealing with different situations, interpersonal relationship within workplace and people along with or without their family and personal problems will lead to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed employees' experience stress due to a series of big changes took place in financial sector as a result of deregulated markets and globalization of economy affect the working lives of bank employees (Kaur et al, 2017;Hassard et al, 2017). On the other hand, employees' personal and social life affected by job stressors might be attributed to responsibilities for people, poor-peer relations and strenuous working conditions that revealed inverse correlation with performance (Valente et al, 2015;Petarli et al, 2015;Snorradottir et al, 2013;Silva & Navarro, 2012). Further employees' need deficiencies and performance have shown inverse relationship might be attributed to low scores on esteem need, autonomy need, self-actualization need and total-need deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A series of big changes took place in financial sector as a result of deregulated and markets globalization of economy affect the working lives of bank employees (Kaur et al, 2017;Hassard et al, 2017). Several studies conducted on banking sector employees using different parameters of stress and revealed that job stress, occupational stress and workplace stress have reported serious issues to the banking sector on employees and put negative effect on employees' health, motivation, adjustment and performance (Petarli et al, 2015;Snorradottir et al, 2013;Silva & Navarro, 2012). Gender was also found important factor of stress (Li et al, 2015;Amigo et al, 2014).…”
Section: Review Of Literaturementioning
confidence: 99%
“…En el estudio del estado del arte, se evidencia una gran variedad de enfoques sobre OT (Garcia Remus & Junco Campos, 2011;Jurado Jurado, 2015;Marsán Castellanos, et al, 1999;Maynard, 2006;Niebel & Freivalds, 2009;Ormaza Murillo, Félix López, Real Pérez, & Parra Ferié, 2015;Silva & Navarro, 2012), quienes realizan sus aportes sobre la organización científica del trabajo; favoreciendo el punto de partida para los posteriores estudios sobre la temática. De igual modo destacan otros autores que si bien, en su generalidad, no estandarizan el término TH, si orientan sus sobre la planificación del factor humano de forma general y su gestión en el nivel empresarial.…”
Section: La Organización Del Trabajo Conceptos Y Enfoques Fundamentalesunclassified